Role of Bioinformatics in Agriculture - Gajula, M. N. V. Prasad; Kumar, Anuj; Siddiq, E. A.; Polumetla, A. K. (International Journal of Economic Plants, 2016)
Bioinformatics is a practical discipline of science that employs a wide range of computational techniques including sequence analysis, data mining, gene finding, phylogenetic tree construction, prediction of protein structure and function, and interaction networks are only a few to mention. Bioinformatics is the use of computer technology, mathematical algorithms, and statistics with concepts in the life sciences to solve biological problems. The application of bioinformatics is not just limited to any particular research domain in biology. In a developing country like India, bioinformatics has a key role to play in areas like agriculture where it can be used for increasing the volume of the agricultural produce, increasing the nutritional content, and implanting disease resistance etc. The first is in terms of ‘scientific’ merit, where bioinformatics play a key role in the development of the underlying computational concepts and models to convert complex biological data into useful biological and chemical knowledge. The second aspect is of ‘technological’ accountability to manage and integrate huge amounts of heterogeneous data sources from high throughput experimentation. A most important task for bioinformatics is to make sense of the enormous quantities of sequence data as well as structural data that are generated by genome-sequencing projects, proteomics projects, and other large-scale molecular biology efforts.